ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OCB PEGAWAI KONTRAK (STUDI PADA PEGAWAI KONTRAK DI LINGKUNGAN UNIVERSITAS DIPONEGORO SEMARANG) - Arina Ratna Paramita; Mudji Rahardjo; Syuhada Sofian (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
ABSTRACT Human resource is the spear from organizations. Without Human Resource, all of the organization resources can’t process and developed to get profit, and it is happened on government organization too. The government organization has Organizational Citizenship Behavior, who helped the employee included the contract workers on their social working scope. Some factors that needed to determine higher or lower the OCB’s level even contract or permanent workers it is loyalty, obesity and their participation to the organization who covered them. Loyalty, obesity and participation levels of contract workers on government sector is an interesting case to research. This research want to analyze and examine influence factors  to the OCB’s contract workers in government organization, with working satisfaction and Organization behavior as an independent variable and use Working Motivation as an intervening variable. Sample of this research is a contract workers who working at Diponegoro University, Semarang. Whereas,  analysis technique on this research using SEM. Based on the research results, that working satisfaction and organization behavior is positively influential to the contract workers working motivation, whereas working motivation factor with a significant too, that positively influential to the OCB’s contract working. Keywords: working satisfaction; organization behavior; working motivation; contract workers